Contrat et commande publique: les cas des marchés publics au Cameroun - Batoum-Ba-Ngoue, Samuel Théophile (Civil Procedure Review, 2017)
This essay discusses how contracts and their theory fit into public negotiation, and how public norms and public interest can match the private autonomy. The article also discusses the role of the judge in controlling this type of contract.